Spontaneous Expulsion of Ingested Foreign Bodies: Case Series and Review of Literature - Yadav, A.K.; Shrestha, R.S.; Sharma, R.; Khadka, B.; Awale, L.; Malla, G.B. (Birat Journal of Health Sciences, 2017)
Foreign body ingestion is a commonly seen event in emergencies, usually in children, psychiatric patients, chronic alcoholics, drug abusers and the elderly patients with poor fitting dentures as well as the mentally challenged individuals. While ingestion of foreign bodies into Gastrointestinal Tract (GIT) may be accidental (especially in children), or experimental (anal insertion by adults), it may be purely intentional as in smugglers of illicit drugs, jewels and other valuables so as to evade detection by the security. About, 90% of ingested foreign bodies pass through the gastrointestinal tract without complications, 1020% necessitate endoscopic removal, while only 1% of them will finally need surgical intervention. In clinical practice we often face the dilemma of choosing the appropriate treatment modality. We present five cases treated in the emergency ward of B P Koirala Institute of Health Sciences, Dharan, Nepal, emphasizing in a "waiting and close observation" policy. Among these cases, all expelled the foreign body spontaneously in their stool without any complications. Birat Journal of Health Sciences 2016 1(1): 78-82